2017
DOI: 10.1039/c7cp00915a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical reduction of CO2 on graphene supported transition metals – towards single atom catalysts

Abstract: In this study, we have investigated the use of single metal atoms supported on defective graphene as catalysts for the electrochemical reduction of CO using the first-principles approach and the computational hydrogen electrode model. Reaction pathways to produce a variety of C products CO, HCOOH, HCHO, CHOH and CH have been studied in detail for five representative transition metals Ag, Cu, Pd, Pt, and Co. Different pathways were revealed in contrast to those found for metallic crystalline surfaces and nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 35 publications
5
73
0
Order By: Relevance
“…All elementary steps with their free‐energy changes are presented in Table S4 (in the Supporting Information). The free energies of the initial protonation steps for CRR (*CO 2 +H + +e − →*COOH or *CO 2 +H + +e − →*OCHO) and HER (proton–electron pair, H + +e − ) can be calculated to discern the selectivity for CRR and HER . Figure shows the selectivity for CRR versus HER on Ni‐C 3 N 4 , Co‐C 3 N 4 , and Fe‐C 3 N 4 , in which the part below the dashed line are CRR‐selective catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All elementary steps with their free‐energy changes are presented in Table S4 (in the Supporting Information). The free energies of the initial protonation steps for CRR (*CO 2 +H + +e − →*COOH or *CO 2 +H + +e − →*OCHO) and HER (proton–electron pair, H + +e − ) can be calculated to discern the selectivity for CRR and HER . Figure shows the selectivity for CRR versus HER on Ni‐C 3 N 4 , Co‐C 3 N 4 , and Fe‐C 3 N 4 , in which the part below the dashed line are CRR‐selective catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…*OCHO) and HER (proton-electron pair,H + + e À )c an be calculated to discern the selectivity for CRR and HER. [19,20,41,42] Figure 5s hows the selectivity for CRR versusH ER on Ni-C 3 N 4 ,C o-C 3 N 4 ,a nd Fe-C 3 N 4 ,inwhich the part below the dashedline are CRR-selective catalysts. Ther esults show that Ni-C 3 N 4 ,C o-C 3 N 4 ,a nd Fe-C 3 N 4 are CRRs electivew ith only one favorable initial protonation step.…”
Section: Competition Between Crr and Her For Initialprotonationmentioning
confidence: 99%
“…To further validate the competitive relationship between the CO 2 RR and HER, theoretical analyses of CO 2 RR and CO desorption barriers are also performed to compressively understand the catalytic mechanism in electrochemical process . According to the DFT simulations, the electrocatalytic activities and selectivity of CO 2 depends on the kinds of catalysts (such as noble or transition metal catalysts).…”
Section: Electrochemical Applications Of Sagmentioning
confidence: 99%
“…The Be-loaded BN [156] and Cu/Mo doped g-C 3 N 4 [157] have been studied theoretically, showing synergistic effect of both metal and the heteroatoms. [160] Beyond the single metal atom catalytic reaction, Sun's group studied the metal dimers supported by graphene derivatives as the active sites for CO2RR. [158] They predicted that both copper and nearby nitrogen were active sites which could connect with the key intermediates, as displayed in Figure 17b.…”
Section: Carbon-based Materialsmentioning
confidence: 99%
“…Based on similar systems, He et al reported that Ag-and Cu-doped graphene was a potential electrocatalyst for CO2RR to methane and methanol respectively. [160] Beyond the single metal atom catalytic reaction, Sun's group studied the metal dimers supported by graphene derivatives as the active sites for CO2RR. [161,162] Using large-scale screening-based DFT and microkinetics modeling, Cu 2 , CuMn, and CuNi dimers supported on graphene with adjacent vacancies were identified as improved electrocatalysts for CO, CH 4 , and CH 3 OH productions, respectively.…”
Section: Carbon-based Materialsmentioning
confidence: 99%